A Contrastive Perspective on English and Dutch Front Monophthongs (Spectrum, 2023)
This paper explores the front pure vowels of English and Dutch from a contrastive standpoint. It basically aims to quantitatively discover the degree to which English and Dutch front monophthong systems are different from each other and proceeds to make some early yet data-driven predictions about the comparative levels of difficulty that the English-speaking learners of Dutch and the Dutch-speaking learners of English as a foreign language would experience while learning their target languages. Applying the same method designed for a quantitative-contrastive phonemic analysis in the earlier works of 2015 and 2019, the researchers prove that the front monophthong systems of English and Dutch are considerably different (81.82%) from each other and that the acquisition workload is heavier (83.33:80) for English speaking learners of Dutch as a foreign language than it is for Dutch speaking learners of English. In contrast, learners of English will need to generate a greater degree (83.33:80) of substratum counter-influence than learners of Dutch in order to achieve an acceptable level of accuracy in the articulation of their target phonemes. Although both groups of learners retain one vowel sound that occurs as phonetically identical phoneme (16.67:20), the final indication is that the English front monophthong system is likely to pose a greater challenge for its learners.Spectrum, Volume 17, June 2022: 31-46